Structure, costs, and benefits of food subsidies in Bangladesh - Ahmed, Raisuddin (International Food Policy Research Institute, 1988)
Food subsidy is an important element of public policies in Bangladesh. Direct public intervention in foodgrain distribution, now being practiced in Bangladesh, can be traced back to its origin in the 1941-44 wartime food policies of the government of British India in general and of the government of Bengal in particular. War-related disruption in the internal marketing structure, public spending, short supplies, and panic all combined to cause a spiraling of food prices (Sen, 1981). In the wake of impending famine, the government initially reacted by setting maximum prices and coordinating movement of supplies from surplus to deficit areas through private marketing channels.